Check-list and ecology of Sphagnum mosses (Sphagnaceae) in the Republic of Mordovia (Russia) - Oleg G. Grishutkin; Margarita A. Boychuk; Galina A. Grishutkina; Valeria V. Rukavishnikova (Nature Conservation Research, 2020)
Sphagnaceae are an important component of ecosystems. In the forest-steppe zone, where the Republic of Mordovia (Russia) is located, many of these mosses are situated at the edge of the species range. This highlights an importance to research their species diversity and ecology. In this paper, we summarised all available data on Sphagnum species in the Republic of Mordovia. They include literature data, herbarium collections, and results of our own research conducted in 2011–2019. One more task was the compilation of an annotated list of species, analysis of Sphagnum ecology in the Republic of Mordovia. In total, we investigated about 200 mires, swampy and moist lands. We found Sphagnum species on 169 sites where we made 452 geobotanical relevés. We collected and identified about 1450 specimens of Sphagnum species. Of them, 375 specimens are stored in HMNR and GMU. Our study has resulted in an annotated species list containing 26 Sphagnum species, known reliably in the Republic of Mordovia. Such a species diversity is comparable with one in regions of the forest-steppe zone, while the species diversity is lower than in regions of the taiga zone of European Russia. The most frequently occurring species were Sphagnum fallax, S. angustifolium, S. flexuosum, S. squarrosum, S. fimbriatum, S. divinum, S. centrale. Most of the species inhabit transitional mires and bogs. The lower number of species were found in lowland marshes and boggy forests, where Sphagnum mosses are arranged in small clumps and they do not form a solid moss cover. Sphagnum species occur mainly on the terraces of large and medium rivers, as well as on the water-glacial plain. In the other parts of the Republic of Mordovia (landscapes of secondary moraine and erosion-denudation plains), records of Sphagnum species are sporadic. We found quite considerable differences in environmental preferences of Sphagnum species, including habitat illumination, soil moisture, soil trophicity, soil pH, soil nitrogen. The highest variation was noted for Sphagnum ...